Short Temporal Adverbials in English and Macedonian – Semantics, Morphology and Sentence Position - Milenkoska, Jovanka Jovanchevska (Mediterranean Journal of Social Sciences, 2012)
This paper presents a study of short temporal adverbials in English and Macedonian. It includes their semantic, morphologicaland syntactic (sentence position) description. The study and the findings are corpus based, whereas the corpus is composed ofMacedonian literary texts translated by native English speakers. The findings aim at presenting: a) the semantic complexities ofMacedonian temporal adverbs through the usage of English as meta-language, b) the morphological and phrasal forms within whichthese short adverbs occur, and c) the differences/similarities in occupying sentence positions. The study should aid languageprofessionals of different profiles in both, English and Macedonian (theoretical linguists, language teachers, translators, etc.).